TINGKAT EFISIENSI BANK DI INDONESIA - Rubeda Kalis; Pujiati Amin; P. Eko Prasetyo (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
This study aims to analyze the efficiency of banks in Indonesia period 2007-2009.The tools of analysis is Data Envelopment Analysis (DEA). It uses data financial statemens and supplied by Bank Indonesia. The research shows that in general the performance of banks in Indonesia is inefisiency. Bank that have efficiency is BRI, BTN, BPD Jabar, BPD Jatim, BPD Riau, Bank Niaga dan Bank Muamalat. This fact shows the banks in Indonesia have not been up to the wasteful use of cost on several input variables in their economic activities. Key words: Efficiency, bank, Indonesia, DEA